PELAKSANAAN PEMBAYARAN ROYALTI PADA LAGU YANG DIGUNAKAN OLEH RADIO DI PEKANBARU BERDASARKAN PERATURAN PEMERINTAH NOMOR 56 TAHUN 2021 TENTANG PENGELOLAHAN ROYALTI HAK CIPTA LAGU DAN MUSIK - Shofa Rizkina Pratiwi.A; Zulfikar Jayakusuma; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law Number 28 of 2014 concerning copyright, hereinafter referred to as theCopyright Law in Article 1 Paragraph 1, says that copyright is the copyright of thecreator that arises automatically based on the declarative principle after a work isrealized in a tangible form without reducing the complexity in accordance withthe provisions of the legislation. One of the intellectual property products includedin intellectual property rights is a song. The use of songs accompanied by materialbenefits, one of which is in radio media. As quoted from Government RegulationNumber 56 of 2021 Article 3 paragraph (1) that